Sheet-Like Remodeling of the Transverse Tubular System in Human Heart Failure Impairs Excitation-Contraction Coupling and Functional Recovery by Mechanical Unloading. Issue 17 (25th April 2017) - Seidel, Thomas; Navankasattusas, Sutip; Ahmad, Azmi; Diakos, Nikolaos A.; Xu, Weining David; Tristani-Firouzi, Martin; Bonios, Michael J.; Taleb, Iosif; Li, Dean Y.; Selzman, Craig H.; Drakos, Stavros G.; Sachse, Frank B.
Abstract : Background: Cardiac recovery in response to mechanical unloading by left ventricular assist devices (LVADs) has been demonstrated in subgroups of patients with chronic heart failure (HF). Hallmarks of HF are depletion and disorganization of the transverse tubular system (t-system) in cardiomyocytes. Here, we investigated remodeling of the t-system in human end-stage HF and its role in cardiac recovery. Methods: Left ventricular biopsies were obtained from 5 donors and 26 patients with chronic HF undergoing implantation of LVADs. Three-dimensional confocal microscopy and computational image analysis were applied to assess t-system structure, density, and distance of ryanodine receptor clusters to the sarcolemma, including the t-system. Recovery of cardiac function in response to mechanical unloading was assessed by echocardiography during turndown of the LVAD. Results: The majority of HF myocytes showed remarkable t-system remodeling, particularly sheet-like invaginations of the sarcolemma. Circularity of t-system components was decreased in HF versus controls (0.37±0.01 versus 0.46±0.02; P <0.01), and the volume/length ratio was increased in HF (0.36±0.01 versus 0.25±0.02 µm 2 ; P <0.0001). T-system density was reduced in HF, leading to increased ryanodine receptor–sarcolemma distances (0.96±0.05 versus 0.64±0.1 µm; P <0.01). Low ryanodine receptor–sarcolemma distances at the time of LVAD implantation predicted high post-LVAD left ventricular ejection fractions ( P <0.01) and ejection fraction increases during unloading ( P <0.01). Ejection fraction in patients with pre-LVAD ryanodine receptor–sarcolemma distances >1 µm did not improve after mechanical unloading. In addition, calcium transients were recorded in field-stimulated isolated human cardiomyocytes and analyzed with respect to local t-system density. Calcium release in HF myocytes was restricted to regions proximal to the sarcolemma. Local calcium upstroke was delayed (23.9±4.9 versus 10.3±1.7 milliseconds; P <0.05) and more asynchronous (18.1±1.5 versus 8.9±2.2 milliseconds; P <0.01) in HF cells with low t-system density versus cells with high t-system density. Conclusions: The t-system in end-stage human HF presents a characteristic novel phenotype consisting of sheet-like invaginations of the sarcolemma. Our results suggest that the remodeled t-system impairs excitation-contraction coupling and functional recovery during chronic LVAD unloading. An intact t-system at the time of LVAD implantation may constitute a precondition and predictor for functional cardiac recovery after mechanical unloading. Abstract : Supplemental Digital Content is available in the text.